1914
DOI: 10.1037/h0071289
|View full text |Cite
|
Sign up to set email alerts
|

Attention.

Abstract: There are two articles on the general nature of attention. D'AUonnes (1) interprets attention very broadly to mean the general understanding of experiences. He distinguishes four main levels. At the first, sensory attention, the conditions are physiological and unconscious, attention is induced by strong stimuli and accompanied

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1930
1930
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…(For example, as was mentioned in the introduction,having distractor characters flash on and off, much like the objects in the present experiment, weakened, rather than amplified, their distracting power when subjects performed a colorsearch task ; Pashler, in press.) The commonsense view, it would seem, correctly characterizes the attention shifts that occur when the default set is in place (as Folk et al, 1992, conjectured), but traditional writers (such as Pillsbury, 1908, quoted in the first paragraph of this article) incorrectly assumed that these tendencies are fixed. Attention shifts to transients and to unique items should not be described as involuntary, it seems, but rather as contingently involuntary (i.e., the tendency can be voluntarily "turned off " or suppressed when it is not necessary for performing a given task).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(For example, as was mentioned in the introduction,having distractor characters flash on and off, much like the objects in the present experiment, weakened, rather than amplified, their distracting power when subjects performed a colorsearch task ; Pashler, in press.) The commonsense view, it would seem, correctly characterizes the attention shifts that occur when the default set is in place (as Folk et al, 1992, conjectured), but traditional writers (such as Pillsbury, 1908, quoted in the first paragraph of this article) incorrectly assumed that these tendencies are fixed. Attention shifts to transients and to unique items should not be described as involuntary, it seems, but rather as contingently involuntary (i.e., the tendency can be voluntarily "turned off " or suppressed when it is not necessary for performing a given task).…”
Section: Discussionmentioning
confidence: 99%
“…Titchener (1908), for example, went so far as to claim that any sudden change would distract a person who was trying to concentrate on something else (p. 192), and James (1890/1950) made similar comments. Pillsbury (1908) said "an object in motion in any part of the field of vision will at once attract the attention, and will hold it as long as it continues to move" (p. 48).…”
mentioning
confidence: 99%
“…If consciousness is interpreted as the selective aspect of attention (Kahneman, 1973;Posner & Boies, 197 l), then one is unconscious or unaware of stimuli that impinge on receptors but fall outside the metaphorical spotlight of selective attention. This sense of the conscious-unconscious distinction is supported both by nearly 40 years of modern research on selective attention and by a long tradition in which attention has been a central topic of psychology (e.g., James, 1890;Pillsbury, 1908). The major research questions associated with this attentionless sense of unconscious cognition are, What are the limits of cognitive analysis of registered-but-unattended stimuli?, and What memory residues are established by such stimuli?…”
Section: Two Senses Of Unconsciousmentioning
confidence: 99%
“…Thus, W. B. Pillsbury (1908) proposed that the act of preparing to search might consist, not in some mental operation specific to search per se, but merely in forming a mental image of the target to be searched for. He wrote:…”
mentioning
confidence: 99%
“…
Pillsbury (1908) suggested that deciding to search for something in a scene consists of nothing more than forming a visual image of the target. If so, imaging should trigger search even when it would be more advantageous not to search.
…”
mentioning
confidence: 99%